2013
DOI: 10.1007/jhep03(2013)104
|View full text |Cite
|
Sign up to set email alerts
|

The Pauli exclusion principle at strong coupling: holographic matter and momentum space

Abstract: For free fermions at finite density, the Pauli exclusion principle is responsible for the existence of a Fermi surface and the consequent presence of low energy spectral weight over a finite range of momenta. We investigate the extent to which this effect occurs in strongly interacting quantum matter with a holographic dual. We obtain the low energy current-current spectral weight in two holographic frameworks at finite density: systems exhibiting semi-local quantum criticality (with a low temperature entropy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 75 publications
7
97
0
Order By: Relevance
“…The Bekenstein-Hawking formula applied to the metric (3.14a) or (3.18a), after using the relations (3.22), gives for the entropy density 33) with U T the scale associated to the radius of the horizon (and therefore the temperature) r H .…”
Section: Jhep02(2015)010mentioning
confidence: 99%
See 1 more Smart Citation
“…The Bekenstein-Hawking formula applied to the metric (3.14a) or (3.18a), after using the relations (3.22), gives for the entropy density 33) with U T the scale associated to the radius of the horizon (and therefore the temperature) r H .…”
Section: Jhep02(2015)010mentioning
confidence: 99%
“…This is an indication that there are low-energy degrees of freedom at finite momentum, and suggests a fermionic behavior of the dual theory. To obtain this behavior of the spectral density one must consider the z → ∞ limit with z/θ = −1 [32] (see also [33] for another string theory realization in which z/θ = −1 appears). This is precisely the limit in which the IR fixed point of 4+1 SYM theory with external quark density is obtained.…”
Section: Jhep02(2015)010mentioning
confidence: 99%
“…For hyperscaling-violating geometries, the double scaling limit θ → −∞ and z → ∞ with −θ/z = η > 0 fixed has been studied to some extent due to having a spectral density that is not exponentially suppressed [21]. The spacetime is conformal to AdS 2 × R 2 and appears in near-horizon geometries of dilatonic black holes [88], in addition to having other interesting properties [9,89]. However, in our case we would like to keep z finite and take θ → −∞, which does not seem to have been studied.…”
Section: θ → −∞ and Its Connection To Little String Theorymentioning
confidence: 99%
“…Moreover, while the duality has yielded many striking results, it has also produced many mysteries, such as the fate of Fermi surfaces at strong coupling, explored in e.g. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The 'microscopic' field content of the theories with gravity duals generally includes gauge bosons, fermions, and scalars, with the number of degrees of freedom for all of these scaling as O(N 2 ) in the 4D field theory examples.…”
Section: Jhep06(2014)046mentioning
confidence: 99%
“…Specifically, we will explore the behavior of N = 1 super-QED (sQED) and N = 2 sQED in the presence of chemical potentials at zero temperature. Even these simple toy models show some curious features, since from a condensed-matter point of view they have unusual field content and interactions, with the 3 In [24] it is observed that density-density correlation functions in theories with dual Lifshitz geometries [29,30] with z = ∞ have momentum-space singularities which suggest the presence of a Fermi surface, but z < ∞ examples do not.…”
Section: Jhep06(2014)046mentioning
confidence: 99%